KARAKTERISTIK MUTU SNACK BAR TINGGI PROTEIN BERBASIS TEPUNG JAGUNG DAN BIJI KETAPANG - Febrianza, Herry; Widawati, Lina; Nur'aini, Hesti (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
Corn and ketapang seeds can be processed into snack bar because they are high in carbohydrates and contain protein and fiber. This research aims to analyze the physical, chemical, organoleptic properties, best formulation of snack bars based on corn flour and ketapang seeds. In this study, there were 6 variations in the ratio of raw material composition treatments, namely wheat flour: corn flour (0:50; 25:25; 50:0) and the addition of ketapang seeds (25, 50). The research results show that the average yield for snack bars is between 64.29% and 73.81%. The highest average snack bar texture was in the composition treatment of wheat flour: corn flour: ketapang seeds 0:50:25, namely 3.34 mm. The lowest average water content of snack bars was in the composition treatment of wheat flour: corn flour: ketapang seeds 25:25:25, namely 18.78%. The highest average protein content of snack bars in the treatment composition of wheat flour: corn flour: ketapang seeds 0:50:50 was 9.28%. The best formulation of snack bar based on organoleptic parameters is the treatment of the composition of wheat flour: corn flour: ketapang seeds 0:50:50 with a color value of 3.65 (like), taste 3.65 (like), aroma 3.80 (like, and texture 3.95 (like).